Federal Enactment of Healthy Homes Legislation in the United States to Improve Public Health - Ferguson, Alesia Coralie; Yates, Christopher (Frontiers in Public Health, 2016)
Not all homes across America are “healthy” homes. This contributes to the poor health of Americans and exacerbates existing health conditions costing millions each year in health-care cost. Newer research is being conducted into strategies to alleviate biological, chemical, and physical hazards in the home, and various programs exist to assist the homeowner in making improvements in the quality of their home. Not every homeowner or renter nationwide or within community localities has access to these strategies or programs that could potentially improve their home environment and therefore the health of their family. The objective of this article is to propose elements of a policy to address this inconsistency and variation. This proposal centers around the federal enactment of a national policy demanding that each state implements a healthy homes program tailored to fit their specific state housing and health needs. Members of Congress from States that have successfully implemented healthy home programs should champion this policy. Organizations that recognize the impact of housing on health should support the development of a national healthy homes strategy. This article will discuss the need, outcomes, stakeholders, and minimum requirements of such a policy.